eCM 2018
DOI: 10.22203/ecm.v036a01
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of ENPP1 by osterix in osteoblasts and osteocytes

Abstract: Ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) is the main source of extracellular pyrophosphate. Along with tissue-nonspecific alkaline phosphatase (TNAP), ENPP1 plays an important role in balancing bone mineralisation. Although well established in pre-osteoblasts, the regulating mechanisms of ENPP1 in osteoblasts and osteocytes remain largely unknown. Using bioinformatic methods, osterix (Osx), an essential transcription factor in osteoblast differentiation and osteocyte function, was found to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…During OM induction, the expression of MMP7 was enhanced, while the expression of MMP1 was repressed; these findings indicate that MMP7, instead of MMP1, is involved in OM-induced matrix remodeling. In addition, the expression of ENPP1, which produces an inhibitor of hydroxyapatite crystal formation (pyrophosphate, PPi), is a regulator of the phosphate/PPi ratio [ 66 ], was specifically upregulated by OM. Other bone resorption promotors, including ADAMTS1, MGP and CTSK, were also upregulated to accelerate mineralization remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…During OM induction, the expression of MMP7 was enhanced, while the expression of MMP1 was repressed; these findings indicate that MMP7, instead of MMP1, is involved in OM-induced matrix remodeling. In addition, the expression of ENPP1, which produces an inhibitor of hydroxyapatite crystal formation (pyrophosphate, PPi), is a regulator of the phosphate/PPi ratio [ 66 ], was specifically upregulated by OM. Other bone resorption promotors, including ADAMTS1, MGP and CTSK, were also upregulated to accelerate mineralization remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…Sp7 has been shown to upregulate transcription of various osteoblast-related genes, including Fmod (fibromodulin) [ 29 ], Col1a1 [ 30 , 31 ], Col1a2 [ 32 ], Col5a1 [ 33 ], Col5a3 [ 34 ], Ibsp [ 29 , 35 ], Sost [ 13 , 36 ], Bglap [ 37 ], Zbtb16 [ 38 ], Cx43 [ 39 ], Vegf (vascular endothelial growth factor) [ 40 ], Mmp9 (matrix metalloproteinase 9) [ 41 ], Mmp13 (matrix metalloproteinase 13) [ 42 , 43 ], Zip1 [ 44 ], Ucma (upper zone of growth plate and cartilage matrix associated) [ 45 ], and Enpp1 (pyrophosphatase/phosphodiesterase 1) [ 46 ] (extensively reviewed in [ 47 ]). This series of studies demonstrated that Sp7 bound to the typical GC-box (Sp1-binding sites) or CCAAT sequences around these genes ( Figure 1 ).…”
Section: Targets Of Sp7 In Osteoblastsmentioning
confidence: 99%
“…Osx can also interact with Runx2 to coordinately activate the expression of the various genes, and their synergistic effects achieve significantly higher expression levels than those obtained with the individual expression vectors. Col1a1, Sost, Ectonucleotide pyrophosphatase/phosphodiesterase 1(Enpp1) and the novel gene unique cartilage matrix-associated protein (Ucma) have been reported to be their coordinated target genes (Ortuno et al, 2013;Lee Y. J. et al, 2015;Pérez-Campo et al, 2016;Gao M. et al, 2018). The interaction of Osx and Runx2 in the regulation of these promoters is mediated by Osx's enhancer regions adjacent to Sp1 and Runx2 DNA-binding sites, thereby synergistically regulating those downstream genes transcription.…”
Section: Osx Promotes Osteogenesis Through the Regulation Of Downstream Factorsmentioning
confidence: 99%